The effectiveness of using e-learning in Malaysian higher education: A case study universiti Teknologi Malaysia - Al-Rahmi, Waleed Mugahed (Mediterranean Center of Social and Educational Research, 2015)
E-Learning is a fairly recent word used to define a form of learning that can be performed via websites online learning. The impact of contingent factors on the relationship between six predictors and e-learning effectiveness was investigated. The development and implementation of e-learning today has become an important phases in university. This study is centered on evaluating the e-learning effectiveness in UTM. And in this study, the critical factors affecting e-learning effectiveness were investigated through a survey conducted on students as participants. A total of 268 Universiti Teknologi Malaysia (UTM) (undergraduate students) students were used in the survey. Several factors have been found to correlate with e-learning effectiveness which includes self-efficacy, interface, community, usefulness, students’ satisfaction and intention to use elearning. The results show that e-learning use positively and significantly related to students' satisfaction, usefulness that is impact intention to use in turn affect e-learning effectiveness.